ANALISIS RANCANGAN OPERASI SISTEM PEMBANGKIT LISTRIK TENAGA HYBRID (PLTS – PLTB) ENERGI TERBARUKAN PADA GEDUNG BERSAMA TEKNIK ELEKTRO UNIVERSITAS BRAWIJAYA - Hidayat, n/a; Nurwati, Tri; Wibawa, Unggul (Jurnal Mahasiswa TEUB, 2024)
The increasing need for energy sources is not commensurate with the limited nature of fossil energy, so a transition to renewable energy is needed. However, the availability of renewable energy for electricity generation is still limited and expensive. To overcome this, a combination or hybrid of several power plants is needed. Hybrid operation has long been known as a solution to increase the amount of power generation from renewable energy plants. The aim of this research was to determine the results of designing a hybrid system (PLTSPLTB) using hybrid design software and analyzing it from technical and economic aspects. The method used is in the form of calculations on technical and economic aspects through parameters in the form of average hourlyload, solar radiation, wind speed as well as component specification and price data. Based on the results of operating system design using hybrid design software, it was found that the results of optimizing solar panels with a capacity of 2.75 kW, 1 wind turbine, 4 kW inverter, and connected to the PLN grid produce electrical energy of 11,910 kWh/year and renewable penetration of 41.5%. When installing a hybrid system (PLTS-PLTB), the energy purchased to the PLN network is 6,968 kWh and the energy sold to the network is 1,235 kWh for one year. From a technical aspect, it requires 10 solar panels with 5 solar panels installed in series and 2 solar panels installed parallel, the highest average solar panel output power occurred in September at 13.52332 kW and the lowest average output power occurred in February at 9.89158 kW. The highest average output power of wind turbines occurred in September at 196.583 W or 0.197 kW and the lowest average output power occurred in March at 15.625 W or 0.0156 kW. From the economic aspect, the results show a Net Present Cost (NPC) of IDR 252,264,302.01, Total Annualized Cost (TAC) of IDR 14,981,718.67, Cost of Energy (COE) of IDR 1,268.45 per kWh. Keywords: Hybrid operation, Calculation, Solar radiation, Wind speed.